Complementary, alternative, and integrative medicine therapies for knee osteoarthritis: a visual analytics analysis of the research domain - Chuqing Luo; Chuqing Luo; Jing Wang; Jing Wang; Jiaojiao Guo; Jiaojiao Guo (Frontiers in Medicine)
IntroductionKnee osteoarthritis (KOA) affects 528 million people globally, with prevalence projected to rise by 74.9% by 2050. Traditional treatments face limitations in long-term safety and efficacy, driving interest in complementary, alternative, and integrative medicine therapies (CAIMT) for symptom relief and disease management. This article present an analysis of this research domain.MethodsA systematic search of Web of Science (1994–2024) identified 1,389 publications using CAIMT-related keywords. Bibliometric tools analyzed publication volume, citations, authorship, institutional collaborations, geographical distribution, keyword co-occurrence, and thematic evolution. Metrics assessed academic impact, and Bradford's Law identified core journals.ResultsPublications surged post-2010, peaking in 2022 (123 papers). China (345 publications) and the USA (282 publications) dominated output. International co-authorship comprised 22.46%. Bennell K. L. (n = 39), Hinman R. S. (n = 29), and Henriksen M. (n = 13) were top authors. The University of Melbourne led institutional contributions. Keyword analysis revealed eight clusters: such as Pain management, exercise/rehabilitation, Nutritional interventions, Emerging therapies. Thematic Evolution: Focus shifted from singular therapies pre-2010 to integrative strategies post-2020, emphasizing personalized and evidence-based approaches.ConclusionCAIMT offers promising adjunctive strategies for KOA management, particularly for aging populations seeking non-pharmacological options. Future research should prioritize personalized, integrative approaches and rigorous evidence generation to refine clinical guidelines.